A DNAzyme-mediated logic gate for programming molecular capture and release on DNA origami. Issue 54 (23rd May 2016) - Li, Feiran; Chen, Haorong; Pan, Jing; Cha, Tae-Gon; Medintz, Igor L.; Choi, Jong Hyun
Abstract : Here we design a DNA origami-based site-specific molecular capture and release platform operated by a DNAzyme-mediated logic gate process. Abstract : Here we design a DNA origami-based site-specific molecular capture and release platform operated by a DNAzyme-mediated logic gate process. We show the programmability and versatility of this platform with small molecules, proteins, and nanoparticles, which may also be controlled by external light signals.